Pengembangan Strategi Promosi Madu Galo-galo UMKM Usaha Bukik Nabu (UBUNA) - Henny Herwina; Jasmi Jasmi; Eli Ratni; Wellyalina Wellyalina; Elni Fatimah; Nadira Nurul Fathiyah; Maya Sari; Feskaharni Alamsjah; Putra Santoso (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2023)
Stingless bee cultivation in Indonesia, one of which is in West Sumatra, has the potential as an effort to improve the community's economy. Stingless bees, commonly called Galo-galo, can produce honey, propolis, and bee pollen, which have many benefits and produce high selling power. The community service activity accompanying the Bukik Nabu Business (UBUNA) aimed to develop the Galo-galo cultivation business in the Limau Manis village. This village has optimum natural conditions to cultivate stingless bees due to the availability of feed plant surroundings. The method used directly assisted the development of Micro, Small and Medium Enterprises of UBUNA. It started by adding the number of colonies to the community, harvesting independently on the type of Heterotrigona itama and Geniotrigona thoracica, upscaling branding, making product labels, product promotions, legality, and participating in collaborative events and festivals.